Effect of nodule count and austempering heat treatment on segregation behavior of alloying elements in ductile cast iron - E. Akbarzadeh Chiniforush (China Foundry, 2016)
The equilibrium partition ratio, k, has been measured for Mn, Mo, Si, Ni and Cu in a ductile iron with composition (wt.%): 3.45C, 0.25Mn, 0.25Mo, 2.45Si, 0.5Ni and 0.5Cu with different nodule counts obtained from different section sizes of 13, 25, 75 mm in the as cast, austenitized (at 870 °C for times 1, 4 and 6 hours) and austempered (at 375 °C for times 1 to 1,440 min) samples. Results show that Mn and Mo segregate positively at cell boundaries, but Si, Ni and Cu concentrate in an inverse manner in the vicinity of graphite nodules and there is a depletion of these elements at cell boundaries. Segregation curves for Ni and Cu are more smooth than for Si. Carbide formation has been observed at cell boundaries. Based on the results, the partition ratios for all elements decrease with increasing the nodule count. More carbide with coarser morphology has been observed in the microstructure with a lower nodule count. Austenitization for a longer time can decrease partition ratio, but cannot eliminate it entirely. Increasing the austenitization temperature has the same effect. Austenitizing parameters have no significant effect on carbides volume fraction. The kinetics of austempering is faster in higher nodule counts and subsequently better mechanical properties including higher ductility, strength and toughness have been observed for all austempering conditions studied.